The Effect of Green Innovation on Business Sustainability Through Green Supply Chain Management as a Mediating Variable in Furniture SMEs in Yogyakarta Special Region - Kurniawan, Wahyu; Kusmantini, Titik; Sugandini, Dyah (West Science Business and Management, 2024)
This study shows how business sustainability (SB) is affected by Green Innovation (GI) and uses the mediating role of Green Supply Chain Management (GSCM) to explain the relationship. Quantitative descriptive method was used in this study. The population of this study is all owners and managers of furniture SMEs in the Special Region of Yogyakarta. The data analysis method used in this research is SmartPLS 3. The results showed that: 1) GI has an influence on Business Sustainability; 2) GI has an influence on GSCM; 3) GSCM has an influence on Business Sustainability; 4) GSCM mediates the influence of GI on the Sustainability of furniture SMEs in the Special Region of Yogyakarta.